Analisis Pengaruh Investasi, Inflasi Dan Kurs Terhadap Ekspor Di Indonesia - Erika Miranda; Puti Andiny (Jurnal Samudra Ekonomika, 2022)
This study aims to examine the effect of investment, inflation, and exchange rates on exports in Indonesia simultaneously or partially in 2006-2020. This research uses multiple linear regression analysis method with time series data. The results of the analysis in this study show that investment, inflation and the exchange rate simultaneously affect exports in Indonesia in 2006-2020. Then partially, investment and inflation have a positive and significant effect on exports in Indonesia. While the exchange rate has a negative and significant effect on exports in Indonesia in 2006-2020. The coefficient of determination (R2) obtained in this study is that investment, inflation and the exchange rate affect exports in Indonesia by 90.21%.